Overseers of Upper Egypt in the Old to Middle Kingdoms - Brovarski, Edward (Zeitschrift für ägyptische Sprache und Altertumskunde, 2013)
Some 85 overseers of Upper Egypt are known in the period extending from the Old Kingdom through the Middle Kingdom. The present article provides an inventory of the holders of the title, discusses the dating of the individuals concerned, and the significance of the titles in these different eras.